Pengaruh Pendekatan Realistik Dalam Pembelajaran Matematika Terhadap Pemecahan Masalah Siswa SD (International Forum of Researchers and Lecturers, 2024)
This study aims to analyze the effect of the Realistic Mathematics Education (RME) approach on the mathematical problem-solving abilities of elementary school students. RME is a learning approach that connects mathematical concepts with real situations that students can find in everyday life. The research method used is qualitative research by reviewing the results of previous studies that are relevant in the context of mathematics learning in elementary schools. Based on the analysis of various studies, the results of the study indicate that the application of RME can improve students' mathematical problem-solving abilities. This is evident in various materials such as geometry (circumference and area of ​​trapezoids and kites), mixed arithmetic operations, and equivalent fractions. RME also plays a role in increasing students' self-esteem and self-efficacy in learning mathematics, which in turn strengthens their motivation and performance. In addition, the learning media used in RME, such as geoboards, can enrich students' learning experiences and facilitate understanding of mathematical concepts in a more concrete way. This study provides an overview that RME not only improves students' cognitive abilities, but also supports their emotional and social development in the context of mathematics learning.